PENGARUH VARIASI JENIS AIR DAN KONDISI AKTIVASI DARI ADSORBEN FLY ASH BATU BARA TERHADAP PRESTASI MESIN DAN KANDUNGAN EMISI GAS BUANG SEPEDA MOTOR KARBURATOR 4-LANGKAH - Denfi Efendri; Herry Wardono (Jurnal Ilmiah Teknik Mesin, 2014)
The activated fly ash of coal as adsorbent pellets can be used to save fuel consumption. This research is done with some testing that is the runs test (road test and acceleration), stationary and emission testing. Fly Ash pellets packed in a frame and put on the air filter absolute revo 110 cc motorcycle. So before the air filter into the vehicle, it wil be contact with the pellets Fly Ash first. In this study, the most efficient types of water used is H12 Z20 and the best conditions was on the temperature 150o C and activation time of 1 hour with fuel savings in road test reached 12.69%, and fuel economy at a stationary test up to 22.65% and the reduction of travel time ( 0-80 km/h ) of 6.86%. Fly Ash pellets are able to reduce the levels of CO by 76,92 %, 19,57 % for HC levels and raise their levels of CO by 4,36 %.Keywords : Fly ash adsorbent pellets, engine performance, exhaust gas emissions